SPEAKING CLASSROOM INTERACTION BASED ON INITIATION-RESPONSE-FEEDBACK (IRF) MODEL FOR GRADE VIII AT SMP NEGERI 16 MEDAN - Ekam Sehari Manalu; Rika Rika; Tiarnita Maria Sarjani Br. Siregar (Universitas Negeri Medan, 2019)
This study was about Speaking Classroom Interaction Based on Initiation-Response-Feedback (IRF) Model for Grade VIII at SMP Negeri 16 Medan. The aim of this study were to state clearly the objectives of the study in relation of the problem posed. The objective was to describe how the pattern of IRF in the speaking classroom interaction for students grade VIII at SMP Negeri 16 Medan. This research used qualitative research. The data were collected in two ways by observing by video recording and interviewing. The data was analyzed based on Sinclair and Coulthard theory (1975). The results of this study were the following (1) The language used by the teacher and the students in the classroom interaction was not balance. They are seldom to use English. Both teacher and students used Bahasa for 57% and the rest 43% they use English. (2) The lowest pattern was the teacher’s feedback. It had 22% feedback given by the teacher to the students. The students’ response was the dominant pattern in the classroom interaction rather than initiation. The students’ response had 44%, while the teacher’s initiation had 34%. This pattern happened when the teacher asked students the examples of using ‘can’ and to do some exercises of using ‘can’ in sentences.